2020
DOI: 10.1186/s13063-020-4231-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of xenon and dexmedetomidine as adjuncts for general anesthesia on postoperative emergence delirium after elective cardiac catheterization in children: study protocol for a randomized, controlled, pilot trial

Abstract: Background: Emergence delirium, a manifestation of acute postoperative brain dysfunction, is frequently observed after pediatric anesthesia and has been associated with the use of sevoflurane. Both xenon and dexmedetomidine possess numerous desirable properties for the anesthesia of children with congenital heart disease, including hemodynamic stability, lack of neurotoxicity, and a reduced incidence of emergence delirium. Combining both drugs has never been studied as a balanced-anesthesia technique. This com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Dexmedetomidine is an agonist of the α 2 adrenergic receptor [ 6 ]. The literature [ 7 ] found in the in vitro study of frog sciatic nerve conduction with high concentration of dexmedetomidine that the reduction of the compound's action potential is concentration-dependent rather than α 2 mediated. In vivo and in vitro studies have found that the effect of clonidine, another α 2 adrenergic receptor agonist, on peripheral nerves may be mediated by blocking the cation current activated by hyperpolarization, rather than due to the agonistic effects of α 2 adrenergic receptors.…”
Section: Related Workmentioning
confidence: 99%
“…Dexmedetomidine is an agonist of the α 2 adrenergic receptor [ 6 ]. The literature [ 7 ] found in the in vitro study of frog sciatic nerve conduction with high concentration of dexmedetomidine that the reduction of the compound's action potential is concentration-dependent rather than α 2 mediated. In vivo and in vitro studies have found that the effect of clonidine, another α 2 adrenergic receptor agonist, on peripheral nerves may be mediated by blocking the cation current activated by hyperpolarization, rather than due to the agonistic effects of α 2 adrenergic receptors.…”
Section: Related Workmentioning
confidence: 99%
“…Continuous improvement of extraction techniques has already reduced the price to a comparable level with other inhaled anesthetics [31]. Xenon would be favored over other anesthetics in high-risk surgeries [4] and is currently in a clinical trial for use in pediatric surgery [32]. Consequently, unraveling the pharmacological mechanism of how xenon produces sedation and anesthesia helps to assess its clinical use regarding the application to patients' risk and safety.…”
Section: Discussionmentioning
confidence: 99%
“…For example, delirium is a behavioral disturbance in the child, which is characterized by crying, thrashing, inconsolability, and disorientation in the early postanesthetic period. 10,11 We considered that observation of postoperative behavior and complications could better assess the safety of dexmedetomidine in children. Although generally considered to be minor adverse effects, PONV is a common postoperative adverse reaction that may increase patient discomfort, cause severe complications, and delay patient discharge.…”
Section: Introductionmentioning
confidence: 99%